TEOLOGI PRIBUMI DI INDONESIA - Karman, Yonky (Jurnal Amanat Agung, 2022)
Abstract: One of the problems with the indigenization of Christian theology in Indonesia is how to respond positively to the Indonesian context. This problem is inseparable from Indonesian theologies which in many respects depend on the final product of Western theologies, a dependence on doing theology without independence and creativity. To overcome this dependence and at the same time foster theological independence, it is first important to reposition the passive subject of doing theology into an active subject by adopting a cultural approach (constructive orientalism). Second, getting rid of the tendency to disbelieve in local elements by reviewing the "kafir" vocabulary of Indonesian Bible texts because these inaccurate translations indirectly reinforce this tendency. Within the context of the church and society, the path of indigenous theology branches off, either through biblical studies or directly through existing church theology. Keywords: indigenization, kafir, independence, Bible, theology. Abstrak: Salah satu problem pribumisasi teologi Kristen di Indonesia adalah bagaimana merespons positif konteks keindonesiaan. Problem ini tak terlepas dari teologi-teologi Indonesia yang dalam banyak hal bergantung pada produk akhir teologi-teologi Barat, suatu ketergantungan berteologi tanpa kemandirian dan kreativitas. Untuk mengatasi ketergantungan ini sekaligus menumbuhkan kemandirian berteologi, pertama-tama pentinglah reposisi subjek pasif berteologi menjadi subjek aktif dengan mengadopsi suatu pendekatan budaya (orientalisme konstruktif). Kedua, menyingkirkan kecenderungan mengafirkan unsur-unsur lokal dengan mengkaji kosakata “kafir” teks-teks Alkitab bahasa Indonesia karena terjemahan yang tak tepat ini secara tidak langsung memperkuat kecenderungan tersebut. Dalam bingkai konteks gereja dan masyarakat, jalan berteologi pribumi bercabang, bisa lewat studi biblika atau langsung lewat teologi gereja yang ada. Kata-kata Kunci: pribumisasi, kafir, kemandirian, Alkitab, teologi.